A new look at acid catalyzed deacetylation of carbohydrates: A regioselective synthesis and reactivity of 2-O-acetyl aryl glycopyranosides. (22nd March 2018) - Stepanova, Elena V.; Nagornaya, Marina O.; Filimonov, Victor D.; Valiev, Rashid R.; Belyanin, Maxim L.; Drozdova, Anna K.; Cherepanov, Victor N.
Abstract: In the present work we report that acetyl groups of per – acetylated aryl glycosides have different reactivity during the acidic deacetylation using HCl/EtOH in CHCl3, which leads to preferential deacetylation at O-3, O-4 and O-6. Thereby, the one-step preparation of 2-O-acetyl aryl glycosides with simple aglycon was accomplished for the first time. It was proved that the found reagent is to be general and unique for the preparation of series of 2-О-acetyl aryl glycosides. We have determined the influence of both carbohydrate moiety and the aglycon on the selectivity of deacetylation reaction by kinetic experiments. Using DFT/B3LYP/6-31G(d, p) and semi-empirical АМ1 methods we have found that the highest activation barrier is for 2-О-acetyl group. This completely explains the least reactivity of 2-О-acetyl group. Graphical abstract: Highlights: Different reactivity of acetyl groups of glycosides in acid-catalyzed deacetylation. Regioselective preparation of 2-O-acetyl aryl glycosides was accomplished. The influence of carbohydrate structure on regioselectivity of deacetylation. Different reactivity of Ac groups is explained by activation barriers.